Problems that patients feel are appropriate to discuss with their GPs. - Spence, S J (1992)
A descriptive study was performed to discover what problems patients felt it appropriate to discuss with their general practitioner, their use of alternative therapies, and any questions they wished their doctor had asked them in the past. Demographic data was recorded including Church attendance. Data was collected using an original questionnaire distributed to two groups of patients; 150 consecutive patients attending the surgery (surgery group) and 220 randomly selected from the adult age-sex register (home group). Chi-squared analysis was performed. A broad range of subjects appropriate to a general practice consultation was found (from influenza to spiritual problems). Prior use of homeopathy and hypnosis was widespread. Multiple attenders were more likely to be church attenders. Men in the surgery group were most likely to discuss marital, relationship and spiritual problems. Qualitative data from open questions demonstrated patients' concerns with consultation time and the exploration of feelings.